Re: Quarantine for returnees and new arrivals from China - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the quarantine schedule for returnees and new arrivals from China to prevent corona infection at BRACU new campus project site.